Spironolactone treatment attenuates vascular dysfunction in type 2 diabetic mice by decreasing oxidative stress and restoring NO/GC signaling - Silva, Marcondes A. B.; Bruder-Nascimento, Thiago; Cau, Stefany B. A.; Lopes, Rheure A. M.; Mestriner, Fabiola L. A. C.; Fais, Rafael S.; Touyz, Rhian M.; Tostes, Rita C. (Frontiers in Physiology, 2015)
Type 2 diabetes (DM2) increases the risk of cardiovascular disease. Aldosterone, which has pro-oxidative and pro-inflammatory effects in the cardiovascular system, is positively regulated in DM2. We assessed whether blockade of mineralocorticoid receptors (MR) with spironolactone decreases ROS-associated vascular dysfunction and improves vascular NO signaling in diabetes. Leptin receptor knockout [LepRdb/LepRdb (db/db)] mice, a model of DM2, and their counterpart controls [LepRdb/LepR+, (db/+) mice] received spironolactone (50 mg/kg body weight/day) or vehicle (ethanol 1%) via oral per gavage for 6 weeks. Spironolactone treatment abolished the endothelial dysfunction and increased endothelial nitric oxide synthase (eNOS) phosphorylation (Ser1177), determined by acetylcholine-induced relaxation and Western Blot analysis, respectively. MR antagonist therapy also abrogated augmented ROS-generation in aorta from diabetic mice, determined by lucigenin luminescence assay. Spironolactone treatment increased superoxide dismutase-1 (SOD1) and catalase expression, improved sodium nitroprusside (SNP) and BAY 41-2272-induced relaxation, as well as increased soluble guanylyl cyclase (sGC) subunit β protein expression in arteries from db/db mice. Our results demonstrate that spironolactone decreases diabetes-associated vascular oxidative stress and prevents vascular dysfunction through processes involving increased expression of antioxidant enzymes and sGC. These findings further elucidate redox-sensitive mechanisms whereby spironolactone protects against vascular injury in diabetes.